Wireless energy consumption optimisation using node coverage controlling in linear-type network. (11th November 2020) - Xin, Gaifang; Zhu, Jun; Luo, Chengming; Tang, Jing; Li, Wei
With the mushrooming development of automatic, intelligent and unmanned technologies, the application of wireless sensor network has become a hot topic. There is a kind of narrow-band structure, such as corridor or tunnel, which needs to use wireless sensor network for parameter sensing. To address unbalanced energy consumption of wireless nodes along length direction, this paper proposes a coverage controlling strategy, and linear-type network is built using several wireless nodes. A base station node is equipped in narrow band structures. Firstly, the wireless perception models are analysed aiming at special monitoring environments, which contain routing path, coverage model, link load and data credible rate; secondly, the survival lifetime of linear-type network is solved based on energy consumption of every wireless node; thirdly, considering the accidental death of deployed nodes, time-sharing scheduling strategy is designed to guarantee the stability of monitoring linear-type network; finally, the experimental results show that the proposed coverage control strategy can optimise the survival lifetime and the energy efficiency of linear-type network, which can provide the reference for node coverage in linear structures.